2010
DOI: 10.1007/s00146-009-0253-y
|View full text |Cite
|
Sign up to set email alerts
|

Aurama: caregiver awareness for living independently with an augmented picture frame display

Abstract: Aurama is a system designed to provide peace of mind and a sense of connectedness to adults who care for elderly parents living alone. Aurama monitors the elders at home using unobtrusive sensor technology and collects data about sleeping patterns, weight trends, cognitive abilities and presence at home. The system provides an unobtrusive ambient information display that presents the status of the elder and lets its users inspect long-term data about the well-being of the elder interactively. Aurama was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 15 publications
1
45
0
Order By: Relevance
“…Olivier et al 2009) or to notifications to external people (e.g. alerts or reports sent to relatives Dadlani et al 2010). Figure 6 shows the evolution of the identified high-level processes studied from 2004 to 2013.…”
Section: Intelligent Buildings Internationalmentioning
confidence: 99%
See 2 more Smart Citations
“…Olivier et al 2009) or to notifications to external people (e.g. alerts or reports sent to relatives Dadlani et al 2010). Figure 6 shows the evolution of the identified high-level processes studied from 2004 to 2013.…”
Section: Intelligent Buildings Internationalmentioning
confidence: 99%
“…Lee, Park, and Helal (2009) also focused on indoor localization tools and compared the source, the information to be extracted, and the difficulty for seven different technologies. Dadlani et al (2010) faced the issue of false reading of a radio frequency-based presence detector due to irregular radio frequency field patterns generated within a building, while Biswas et al (2010) observed signal interference from other household electronics. Hallberg et al (2009) proposed to use magnetic field instead, which is less sensitive to the presence of objects in the building environments, whereas Jimenez et al (2013) considered this technology as not reliable in indoor environments due a high sensitivity to metal parts, for example, reinforced walls (Schikhof, Mulder, and Choenni 2010).…”
Section: Necessary Evaluation Of the Building Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gust-bowl [13] reacts to the placement of objects in a bowl, with the aim of bringing together a mother and son, the latter of whom had recently 'flown the nest'. This was followed by Aurama [4], which 'monitors the elders at home using unobtrusive sensor technology and collects data about sleeping patterns, weight trends, cognitive abilities and presence at home' and was designed to also offer assurance, albeit from a different perspective. More recently, Snow-Globe [25] sought to create a social connectedness by changing color to indicate whether or not someone was present at a distant location and thereby tacitly nudging the remote party.…”
Section: Workmentioning
confidence: 99%
“…Thus, communication technologies can help older adults overcome the physical barriers of interacting with their social networks [10]. In addition, recent literature suggests that communication technologies can enhance active aging and sense of independence in older adults [29].…”
Section: Introductionmentioning
confidence: 99%